PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS : USAHA EKSPEDISI TIKI DI KOTA DENPASAR) - Novandy, Marcellus Ivan; Rastini, Ni Made (E-Jurnal Manajemen, 2018)
The purpose of this study was to clarify the effect of service quality on customer loyalty mediated by customer satisfaction. The research was conducted on consumers who have been using the services Tiki expedition in the last year who live in the city of Denpasar. The method used to determine the sample is non-probability is purposive sampling with a sample size of 100 respondents. Data was collected by questionnaire directly spread in the city of Denpasar. The data analysis technique used is the confirmatory factor analysis, path analysis (path analysis) and Sobel test. The results showed that the quality of service, customer satisfaction and customer loyalty and significant positive effect on the decision to use Tiki expedition services in the city of Denpasar.